Synthesis and Evaluation of 1,2,3-Triazole-Containing Vinyl and Allyl Sulfones as Anti-Trypanosomal Agents - Nolan, Derek; McGouran, Joanna; Doherty, William; Adler, Nikoletta; Knox, Andrew; Nikalje, Anna Pratima; Sarkate, Aniket; Lokwani, Deepak; Evans, Paul (My University, 2017)
An approach is described to access 1,2,3‐triazole‐derived peptidyl vinyl sulfones as Trypanosoma brucei brucei inhibitors by using click chemistry, starting from a common azide intermediate. Among the triazole analogues, biotinylated inhibitors 11 and 12 offer possibilities as probes for the elucidation of target proteases for this compound class. The development of two syntheses of a 1,2,3‐triazole‐based vinyl sulfone 5 are also presented. This compound was accessed through a click reaction of a lysine‐derived azide (itself accessed by diazo transfer), and a phenylalanine‐derived alkyne synthesised by both Ohira–Bestmann and Corey–Fuchs‐based alkynylation protocols. Several members of this family of compounds showed promising anti‐trypanosomal activity. Unexpectedly, one of the most active compounds was allyl sulfone 24, which stems from the isomerisation of vinyl sulfone 5, and is presumably a reversible inhibitor. A docking study of the analogues in the active site of the parasitic cysteine protease rhodesain was carried out in order to gain an insight into their likely interactions with these enzymes.
Keywords: Peptidomimetics; Click chemistry; Antiprotozoal agents; Inhibitors; Molecular modeling